ASISTENSI PELAPORAN SURAT PEMBERITAHUAN (SPT) TAHUNAN PAJAK BAGI WAJIB PAJAK PRIBADI DAN BADAN DI SURAKARTA - Widyastuti, Indriana; Rahayu, Saptani; Wisnu Murti, Nugroho (JICS : Journal Of International Community Service, 2024)
The purpose of this Community Service is to find out the assistance of Annual Tax Return Reporting (SPT) for Personal and Corporate Taxpayers in Surakarta. The research location is the Banjarsari sub-district office with several categories of taxpayers including personal taxpayers employees and those who have free work and corporate taxpayers with the category of Micro, Small and Medium Enterprises. The PKM team involved the Tax Volunteer team (Renjani) of Dharma AUB University which amounted to 4 people. The results of Community Service are the addition of the PKM Period Duration and activities carried out on days that are generally the most visited sub-district offices, spread over several weeks. The annual SPT reporting assistance service needs to be socialized through the online media of the local sub-district office. This approach is expected to be more effective than the use of flyer media that was previously carried out. PKM topics need to be adjusted to be more relevant to the needs of the community. This step is to better ensure that the topic presented can attract interest and meet the needs of the community or a more accurate situation analysis.